Temporal and Spatial Distribution of Daily Precipitation Concentration Index in Poyang Lake Basin - LING Ming; XIAO Liying; XU Ming; PENG Daosong; HU Kelong; ZHANG Yue; YAN Ruyu; JI Yong; WANG Yin (Renmin Zhujiang)
Considering the daily precipitation data of 14 meteorological stations in the Poyang Lake Basin from 1957 to 2019,this paper used the precipitation concentration index (CI) to characterize the concentration degree of daily precipitation in the Poyang Lake Basin.After the analysis of the spatial distribution characteristics of the annual average precipitation concentration (ACI) in this basin,the trend of CI was further detected by the Mann-Kendall and Sen's method,and the change-point year of CI was also tested by the Pettitt method.The following conclusions can be drawn from the results:① The ACI of the Poyang Lake Basin increases from south to north,indicating that precipitation in the north of this basin is more concentrated and the probability of extreme precipitation events is also higher in the north;② There is a significant upward trend for the CI at most stations in the east,which means that the precipitation concentration there is increasing;③ A change-point year was observed for the CI at the Jingdezhen Station (in the year of 2006) and the Nancheng Station (in the year of 2009).The average CI after the change-point year is higher than that before the change-point year at both stations,which indicates that in recent years,the daily precipitation at the Jingdezhen Station and the Nancheng Station is highly concentrated in a year.